Bioactive S-PRG materials in dental applications: A clinical evidence–based scoping review - Ferreira, Nathan Felipini; Oliveira Alves, Renata de; Toledo, Priscila Toninatto Alves de; Peres, Georgia Rondó; Danelon, Marcelle; Guiotti, Aimée Maria [UNESP]; Nunes, Gabriel Pereira (Elsevier, 2025)
This scoping review (SR) aimed to map the clinical evidence on the effects of surface pre-reacted glass ionomer (S-PRG)-based materials on dental tissues and performance in restorative, preventive, and therapeutic applications. The SR followed the PRISMA-ScR statement, conducting a comprehensive search across multiple databases for articles published up to January 2025. Out of the 3914 records screened, 49 studies were included in the review. Clinical trials have demonstrated promising outcomes in various dental applications. In caries prevention and white spot lesion management, S-PRG-based sealants and varnishes showed bioactive effects, contributing to remineralization despite limitations in retention. In restorative treatments, S-PRG-based materials showed high clinical success rates, adequate marginal integrity, and minimal postoperative sensitivity, with performance similar to materials without S-PRG fillers. Favorable results were also observed in the treatment of non-carious cervical lesions, dentin hypersensitivity, and molar-incisor hypomineralization, reinforcing the versatility and clinical potential of S-PRG-containing materials. Based on findings, materials containing S-PRG fillers have demonstrated satisfactory clinical performance across various dental applications, especially as restorative agents, sealants, and desensitizers. However, further longer-term clinical studies are needed to confirm their durability, effectiveness over time, and optimize clinical application.